Nedbrydningsfaktorer og restaureringers indflydelse på kalkmaleriers oprindelige udseende - Trampedach, Kirsten (Hikuin, 2007)
The Influence of Deterioration and Restoration on the al State of Wall Paintings By Kirsten Trampedach The medieval wall paintings in Danish churches have changed substantially from the time they were created. These changes have had an important influence on the way the paintings are perceived today and have been caused by different factors: the technique of the paintings, the decomposition of materials and the action of the surrounding climate. Compounding these factors are the interventions of conservators during the last 150 years. Throughout this period various different attitudes pertaining to the conservation/restoration of the paintings have developed. The paintings were executed in a mixed technique, consisting of fresco and secco phase. Quite a number had been initially carried out on a wet ground (lime wash), due to which a fresco effect was achieved, but most frequently the paintings had been created or finished in secco with lime or organic binders (egg, skinglue or oil-based binders). Areas painted in a fresco technique are best preserved, which means that often the visual impression is dominated by red and yellow ochres. Black outlines are missing, pigments are lost and pigments have decomposed – as, for instance, red lead or cinnabar, which change into a black/brown colour, or the blue azurite, which changes into a green copper chloride. The influence of conservators can be seen in restorations carried out from the middle of the nineteenth century until today. In earlier times the greatest importance was attached to the iconographic content, and, as a consequence, the motives were repainted and reconstructed. The conservator of today is much more cautious. Conservation of the material substance is prioritised and retouching is kept to a minimum, and is not executed on original paint layer or ground. Sometimes, however, compromises must be accepted to make the paintings legible, but reconstruction/ retouches are always distinguishable from the original. Preserving wall paintings is a compromise, as the conservator must comply with the demands of the congregation who has the responsibility of the church and its use. This fact can impart severe stress to the wall paintings, due to unfavourable climatic conditions, which are particularly responsible for the deterioration of the paintings. If serious attention is not paid to preventive measures we might one day have to repeat the actions of the past and cover the paintings, this time in order to preserve them for the future!